Comparabilidade dos relatórios financeiros: efeitos na eficiência da transferência de informação nos anúncios de resultados das companhias brasileiras - Reina, Donizete (2021)
The information disclosed by the companies in the companies' results announcements, due to the fact that they contain informational content capable of producing reactions in investors, generate externalities. In the light of the assumptions of the Theory of Disclosure, it is considered that the comparability of financial reports is a predictor of monitoring disclosure patterns, since it is associated with the efficiency of information transfer, in order to minimize the negative effects of the externalities of the ads. results of the companies. In this sense, the general objective of this research is to evaluate the association between the comparability of financial reports and the efficiency in the transfer of information, considering the effects of the externalities of the information around the announcements of results of the companies. Thus, the comparability of financial reports was measured using the similarity model of accounting functions; the transfer of information was obtained through the abnormal volume of trading of the companies, using the event study technique; and the influence of comparability on the efficiency of information transfer was tested by regression analysis with panel data, from 2012 to 2018, in 122 Brazilian companies. As a result, the research showed that: (i) the transport equipment factory sector had the highest levels of average comparability, while that of public utilities was the one with the highest abnormal trading volume; (ii) comparability is positively associated with the market's reaction to the abnormal trading volume, confirming that the companies' results announcements generate externalities of the information, affecting the reaction of investors due to the time of disclosure of the information; (iii) the effect of comparability on the transfer of information does not depend entirely on the number of analysts who monitor the companies; (iv) the interaction of the abnormal trading volume and the comparability with the same auditing company showed that the comparability of the financial reports is associated with the market reaction regarding the abnormal trading volume; and, (v) the comparability of financial reports is associated with the efficiency of information transfer when the company is a leader in the sector. In this sense, it is confirmed the thesis that the comparability of financial reports constitutes a predictor of monitoring the disclosure patterns associated with the efficiency of information transfer, in order to minimize the negative effects of the externalities of the earnings announcements of Brazilian companies.